UPAYA MENINGKATKAN KARAKTER ISLAMI ANAK MELALUI METODE MENGHAFAL HADIST DI PAUD KEJORA DUSUN TEMPOS KUJUR DESA GENGGELANG TAHUN PELAJARAN 2020/2021 - Nuriani, Nani (CV. Lafadz Jaya, 2021)
This study aims to describe efforts to improve children's Islamic character through the method of memorizing hadiths at PAUD Kejora, Tempos Kujur Hamlet, Genggelang Village. This classroom action research (CAR) was conducted in the even semester of the 2020/2021 academic year involving 20 students. The method of memorizing hadiths uses props in the form of gestures and integrates learning themes. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study showed a significant increase in children's Islamic character after the implementation of two cycles. In cycle I, classical completeness reached 50% (BB 2 children, MB 8 children, and BSH 10 children). In cycle II, classical completeness increased to 85% (BB 0 children, MB 3 children, and BSH 17 children). This study proves that the method of memorizing hadiths provides an effective solution in forming the Islamic character of early childhood.